Application of RBAC Model in System Kernel - Guan Keqing; Li Hongxin; Kong Xianli (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In the process of development of some technologies about Ubiquitous computing, the application of embedded intelligent devices is booming. Meanwhile, information security will face more serious threats than before. To improve the security of information terminal’s operation system, this paper analyzed the threats to system’s information security which comes from the abnormal operation by processes, and applied RBAC model into the safety management mechanism of operation system’s kernel. We built an access control model of system’s process, and proposed an implement framework. And the methods of implementation of the model for operation systems were illustrated. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1449